Improving the Accuracy of FFT-based GPGPU Ocean Surface Simulations - Eriksson, Jacob; Wingård, Joakim (My University, 2022)
In this paper, we explore how the current state of the art in real-time ocean simula tions can be improved in terms of simulation accuracy, while preserving performance. Current methods, both in academia and in the industry, simulate an ocean model in frequency space on the GPU, convert said model on an approximately frame-by frame basis to the spatial domain using the Fourier transform, and then read back the resulting heightfield to the CPU as input to the application’s physics engine. We propose a fully GPU-based simulation framework that eliminates these GPU readbacks, successfully eliminating the latency-induced simulation errors present in current solutions, while preserving both ocean interactivity and performance. Along this report we also present a prototype of our framework as an Unreal Engine project. From comparing our proposed framework with the current state of the art, we find: • a significant correction in simulation accuracy of boats and their wakes; • near-equivalent GPU performance and improved CPU performance; • the need to rewrite certain physics behaviors for the GPU that are commonly available as built-in functionality in modern CPU-based physics engines; • an arguably more complicated implementation. We conclude that the errors are significant enough to consider in related work and that the proposed approach is worthwhile investigating further in future work. The prototype code is available at: https://github.com/NeonSky/master-thesis
Keywords: computer graphics; 3D graphics; real-time rendering; Fourier transform; FFT; simulation; GPGPU; interactive; ocean wave spectrum; oceanography